Moral Engines : Exploring the Ethical Drives in Human Life. - Mattingly, Cheryl (WYSE Series in Social Anthropology Ser., 2017)
In the past fifteen years, there has been a virtual explosion of anthropological literature arguing that morality should be considered central to human practice. Out of this explosion new and invigorating conversations have emerged between anthropologists and philosophers. Moral Engines: Exploring the Ethical Drives in Human Life includes essays from some of the foremost voices in the anthropology of morality, offering unique interdisciplinary conversations between anthropologists and philosophers about the moral engines of ethical life, addressing the question: What propels humans to act in light of ethical ideals?